2020
DOI: 10.1002/pip.3385
|View full text |Cite
|
Sign up to set email alerts
|

Designing innovative solutions for solar‐powered electric mobility applications

Abstract: Designing with photovoltaics (PV) is the core focus of this paper which presents the results of a design study on conceptual PV applications for electric mobility systems. This is a relevant direction for new product development because PV technology can contribute to improved features of electric mobility systems not just in terms of CO 2 emissions reduction but also regarding product aesthetics and user experiences.Design studies are multidisciplinary by nature; therefore, in this case technical, user, regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Based on some research, the evaluation of the influence of the PV system weight on the vehicle was made, and a comparison regarding its influence is summarised in Table 5. It is shown that with the new PV system technique [56,57], the PV systems add more weight to the vehicle, which will slightly affect its performance. Consequently, it is possible to say that the benefit of this renewable energy source is assured.…”
Section: Energetic Performance Concerning Each Recharging Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on some research, the evaluation of the influence of the PV system weight on the vehicle was made, and a comparison regarding its influence is summarised in Table 5. It is shown that with the new PV system technique [56,57], the PV systems add more weight to the vehicle, which will slightly affect its performance. Consequently, it is possible to say that the benefit of this renewable energy source is assured.…”
Section: Energetic Performance Concerning Each Recharging Methodsmentioning
confidence: 99%
“…Consequently, it is possible to say that the benefit of this renewable energy source is assured. Nevertheless, it is vital to demonstrate that the vehicle speed factor has a significant influence on the energetic performance, as is demonstrated in [57][58][59] and as is shown in Figure 12, which shows that in a deceleration mode, the PV cells will contribute 100% to the recharging action. Therefore, the percentage in this figure presents the rate of use of each charging system for each speed.…”
Section: Energetic Performance Concerning Each Recharging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the energy harvesting systems, it was found to be an emerging research need to seek more efficient piezoelectric systems to store more electricity, for example in a bicycle battery [117,118]. Likewise, recharging stations with solar panels could be evaluated with new shapes and designs as well as extendable surfaces [132]. Such could mean more expensive lifetime solutions, thus potentially compromising the cost-effectiveness of new micromobility solutions.…”
Section: Micromobility and Public Transport Integration [2]mentioning
confidence: 99%
“…System configuration of a passenger EV with PV cells integrated on the car roof and bonnet [36] The first combinations of solar energy and EVs date as far back as the early 1980s but these initial prototypes served as demonstration vehicles to generate research and public interest in solar-powered vehicles rather than as a transport solution for daily use [37]. It was only recently that automobile manufacturers started to consider this technology as a possible option for powering passenger cars, initially in the form of "solar roofs" for powering the vehicle's air conditioning or heating systems [38], [39].…”
Section: Figure 17mentioning
confidence: 99%